Trakowie w armii rzymskiej - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2011)
Recenzja książki: Mihail Zahariade, The Thracians in the Roman Imperial Army. From the First to the Third Century A.D., Vol. I, Auxilia, National Museum of Roman History, Institute of Archaeology „Vasile Pârvan”, The Center for Military Studies, 2, Mega Publishing House, Cluj-Napoca 2009, 409 s.